“Just a Junior Journalist”: Field Theory and Editorial Photographers’ Gendered Experiences - Somerstein, Rachel (Journalism Practice, 2021)
Women outnumber men in graduate and undergraduate programs in photojournalism and work as photo editors at a number of high-profile publications. But in the field of professional editorial photography, they lag men in pay, legitimacy, and status. Using Bourdieu’s field theory, this paper explores how gender shapes the way women experience, compete in, and negotiate the field, specifically regarding assignments, salary, sexual harassment, and tactics for achieving access to stories. Findings suggest that women use their gender as a competitive advantage however they can, but that negative capital attached to femaleness and femininity persists. The findings are based on semi-structured interviews conducted between 2017 and 2019 with 17 female professional editorial photographers, aged 23–82, who work in a variety of beats.
Keywords: Field theory; Myriam; gender; journalism; photojournalism; women and photography

“She’s just another pretty face:” sexual harassment of female photographers - Somerstein, Rachel (Feminist Media Studies, 2021)
This article examines sexual and gendered harassment among professional female editorial photographers, whose experiences have largely been under-researched. It draws on semi-structured interviews conducted between 2017–2019 with 17 female professional editorial photographers, aged 23–82, who work in a variety of beats. Sixteen of 17 interviewees encountered sexual harassment, with gendered harassment the most common. Harassers included professors, other photographers, colleagues, salespeople, subjects, and the general public, whom photographers encountered at school, work, while networking, and when using and buying gear. Largely, participants addressed the sexual and gendered harassment on an individual level, rather than reporting it to editors or other authorities. These findings add qualitative nuance to quantitative research that suggests physical risks and economic precarity may drive women from the profession.
Keywords: Bibliographie; Embodiment; Myriam; Nettoyer; Sexual harassment; female journalists; gender and work; photographers; photojournalism